A kind of Al-Cu-Mg-Ag-La heat-resistant aluminum alloy material and preparation method thereof

By introducing ZrB2 ceramic particles and rare earth lanthanum into the Al-Cu-Mg-Ag-La alloy, the problem of insufficient strength, toughness and high temperature resistance of aluminum-copper alloys under high performance requirements has been solved, and significant improvements in mechanical properties and Improved productivity.

CN118854112BActive Publication Date: 2025-01-24GUANGXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410901135.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-01-24
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

In areas with high performance requirements such as high-speed trains, existing aluminum-copper alloys are difficult to meet the requirements of strength and toughness and high temperature resistance at the same time.

Method used

ZrB2 ceramic particles were prepared by in-situ reaction of K2ZrF6 and KBF4, and combined with rare earth lanthanum as alloy modifier, which significantly improved the comprehensive properties of Al-Cu-Mg-Ag-La alloy.

Benefits of technology

It significantly improves the hardness, room temperature and high temperature tensile strength of the alloy, overcomes the shortcomings of traditional Al-Cu alloys in casting performance, reduces production costs, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854112B_ABST
    Figure CN118854112B_ABST
Patent Text Reader

Abstract

The invention discloses an Al‑Cu‑Mg‑Ag‑La heat-resistant aluminum alloy material and a preparation method thereof, which belongs to the technical field of alloy materials. The Al‑Cu‑Mg‑Ag‑La heat-resistant aluminum alloy material preparation method comprises the following steps: alloy drying; preparing reactant powder; smelting aluminum blocks; adding reactant powder to aluminum ingot melt, stirring, adding refining agent to remove slag; alloy smelting; modification treatment; cast alloy synthesis; T6 alloy synthesis, the Al‑Cu‑Mg‑Ag‑La heat-resistant aluminum alloy prepared by the invention has excellent hardness and tensile tensile strength, and has excellent mechanical properties at high temperatures. The preparation process of the invention is simple and efficient, reduces production costs, improves production efficiency, is easy to realize industrialized production, and has great application prospects in the fields of new material development and excellent high-temperature resistant alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to an Al-Cu-Mg-Ag-La heat-resistant aluminum alloy material and a preparation method thereof. Background Art

[0002] Aluminum-copper alloys are widely used in aerospace, transportation, marine engineering, military and defense fields due to their low density, high strength, good formability and strong fatigue resistance. However, with the rapid development of high-speed trains, high speed, high safety, light weight and integration have become important development directions, which puts higher requirements on the toughness and high temperature resistance of aluminum-copper alloys. Therefore, it is of great significance to maintain or improve its plasticity, toughness and high temperature resistance while further improving the strength of aluminum-copper alloys.

[0003] At present, the main methods to further improve the strength, toughness, weldability and other properties of aluminum alloys are nanoparticle composite strengthening and rare earth microalloying: (1) Particle-reinforced aluminum-based composite materials, which improve the comprehensive properties of aluminum alloys by introducing ceramic particles as a second phase into aluminum alloys. Compared with the large size and poor interface bonding of the external particle reinforcement phase, the reinforcement particles introduced by in-situ synthesis have good bonding with the matrix and a clean interface without additional products, high thermodynamic stability, and small size (usually at the nanometer to submicron level). They have significant effects on improving the strength, high temperature resistance, corrosion resistance and fatigue resistance of aluminum alloys. However, in-situ synthesized nanoparticles also have the problems of large surface energy and easy agglomeration. Agglomeration caused by too many particles will deteriorate the alloy properties. At present, one of the research hotspots of in-situ reinforcement particles is to effectively and evenly disperse the in-situ synthesized nanoparticles in the matrix to ensure the strengthening effect of the nanoparticles. (2) Rare earth microalloying is another method to improve the comprehensive mechanical properties of aluminum alloys. The introduction of rare earth elements into aluminum alloys can significantly refine the matrix grains while forming a large number of dispersed nano-rare earth precipitates, which improves the toughness, fatigue resistance, creep resistance and high temperature resistance of the alloy. Although many studies have shown that the application of rare earths in aluminum alloys can greatly improve the performance of aluminum alloys, the high cost of rare earths must be considered in practical applications; in addition, excessive addition of rare earths will produce coarse precipitates, which will reduce the performance and limit the application of rare earth microalloying. Summary of the invention

[0004] In view of the problems and shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an Al-Cu-Mg-Ag-La heat-resistant aluminum alloy material and a preparation method thereof. The alloy prepared by the present invention not only has excellent hardness and tensile strength, but also has excellent mechanical properties under high temperature environment.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing an Al-Cu-Mg-Ag-La heat-resistant aluminum alloy material comprises the following steps:

[0007] S1. Alloy drying: cutting aluminum ingots, aluminum-copper alloys, aluminum-magnesium alloys, aluminum-silver alloys, and aluminum-lanthanum alloys into small pieces in a machine tool and drying them;

[0008] S2, K2ZrF6 powder and KBF4 powder are dehydrated and mixed to obtain reactant powder;

[0009] S3, melting aluminum block: placing a pure aluminum ingot in a graphite crucible in a pit-type resistance furnace preheated to 250-300°C and heating it up with the furnace. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0010] S4, adjusting the temperature of the pit-type resistance furnace, adding the reactant powder obtained in step S2 to the aluminum ingot melt in S3, stirring, and adding a refining agent to remove slag;

[0011] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 750-800℃, add the aluminum-copper alloy and aluminum-silver alloy dried in S1 in sequence, add covering agent, let it stand and keep warm for 5-10 minutes, stir and remove slag;

[0012] S6, modification treatment: when the temperature of the pit-type resistance furnace drops to a certain temperature, the aluminum-magnesium alloy and aluminum-lanthanum alloy dried in S1 are quickly pressed into the bottom of the melt for modification treatment. After keeping warm for 5-10 minutes, hexachloroethane is added. After all the raw materials are completely melted, slag is removed again;

[0013] S7, as-cast alloy synthesis: adjust the temperature of the pit-type resistance furnace, perform mechanical stirring, heat up, and when the furnace temperature is maintained at a certain temperature, remove the slag, maintain the temperature and take out the crucible, inject the alloy liquid into the preheated mold, cool it, and demold it to obtain the as-cast Al-Cu-Mg-Ag-La alloy;

[0014] S8, T6 state alloy synthesis: the cast Al-Cu-Mg-Ag-La alloy obtained in step S7 is placed in a muffle furnace and heated to a certain temperature, and the temperature is kept, and cold quenching and solid solution is performed. The water-quenched sample is placed in a muffle furnace and heated to a certain temperature, and the temperature is kept, and then the sample is cooled to room temperature to obtain Al-Cu-Mg-Ag-La heat-resistant aluminum alloy.

[0015] Preferably, in step S1, the heating rate of the drying oven is 5-10°C / min, and the metal block is dried in the drying oven at 200°C for 0.5h.

[0016] Preferably, in step S2, the K2ZrF6 powder and the KBF4 powder are dehydrated at 250-300°C for 3 hours and mixed evenly in a mass ratio of 112:120 to obtain a reactant powder.

[0017] Preferably, in step S3, the pure aluminum ingot is placed in a graphite crucible and heated to 750-800° C. in a preheated pit-type resistance furnace.

[0018] Preferably, in step S4, the temperature of the pit-type resistance furnace is adjusted to 870° C., the reactant powder obtained in step S2 is added to the aluminum ingot melt in S3, stirred for 30 minutes at a stirring rate of 600 r / min using a graphite stirrer, and a refining agent is added to remove the slag.

[0019] Preferably, the amount of reactant powder added in S4 is 1 wt%-7 wt%.

[0020] Further preferably, the addition amount of the reactant powder in S4 is 1 wt%-5 wt%.

[0021] Preferably, in step S4, a graphite rod is used to press the reactant powder into the melt, so as to avoid floating of the reactant powder.

[0022] Preferably, in step S5, the covering agent is a mixture of NaCl and KCl in a mass ratio of 1:1.

[0023] Preferably, in step S6, when the temperature of the pit-type resistance furnace drops to 680-700° C., the aluminum-magnesium alloy and aluminum-lanthanum alloy dried in S1 are quickly pressed into the bottom of the melt for modification.

[0024] Preferably, in step S7, when the temperature of the pit-type resistance furnace is adjusted to 700-710°C, mechanical stirring is performed for 2 minutes, the temperature is increased, and the slag is removed when the furnace temperature is maintained at 730-740°C. The temperature is maintained and the crucible is taken out, the alloy liquid is injected into the preheated mold, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0025] Preferably, after the mold is fully coated with the mixed coating in step S7, it is placed in a muffle furnace and preheated to 200°C.

[0026] Preferably, the mixed coating is a mixture of sodium silicate and zinc oxide in a mass ratio of 1:3.

[0027] Preferably, in step S8, the cast Al-Cu-Mg-Ag-La alloy is placed in a muffle furnace and heated to 520° C. and kept warm for 6 hours, and then quenched in water at 70-100° C. to form a solid solution.

[0028] Preferably, in step S8, the water-quenched sample is placed in a muffle furnace and heated to 170° C. and kept warm for 8 hours.

[0029] The present invention also provides an Al-Cu-Mg-Ag-La heat-resistant aluminum alloy, which is obtained by the preparation method.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention provides an Al-Cu-Mg-Ag heat-resistant aluminum alloy and a preparation method thereof. The ZrB2 ceramic particles with different compositions are prepared by in-situ reaction of K2ZrF6 and KBF4, and the ZrB2 ceramic particles are combined with rare earth lanthanum as an alloy modifier, thereby significantly improving the comprehensive performance of the aluminum-copper-magnesium-silver alloy material. The alloy is significantly improved in terms of Vickers hardness, tensile strength at room temperature and high temperature, and effectively overcomes the shortcomings of traditional Al-Cu alloys in casting performance. In addition, the preparation process of the present invention is simple and efficient, the melting and cooling process time is short, the production cost is reduced, the production efficiency is improved, and industrial production is easy to realize, and it has great application prospects in the fields of new material development and excellent high-temperature resistant alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 XRD line graph of the cast alloy provided in Examples 1-4;

[0033] Figure 2 XRD line graph of the T6 state heat-resistant aluminum alloy provided in Examples 5-8;

[0034] Figure 3 A histogram of Vickers hardness of the as-cast alloys provided for Examples 1-4;

[0035] Figure 4 Room temperature tensile curves of the cast alloys provided in Examples 1-4;

[0036] Figure 5 The high temperature tensile curve of the cast alloy provided in Examples 1-4;

[0037] Figure 6 A Vickers hardness bar graph of the T6 state heat-resistant aluminum alloy provided in Examples 5-8;

[0038] Figure 7 Room temperature tensile curve of the T6 state heat-resistant aluminum alloy provided in Examples 5-8;

[0039] Figure 8 This is a high temperature tensile curve of the T6 heat-resistant aluminum alloy provided in Examples 5-8. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0041] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0042] The raw materials of the present invention are industrial pure aluminum and aluminum-copper 50 alloy provided by Suzhou Guangyuan Metal Materials Co., Ltd.; aluminum-magnesium 20 alloy, aluminum-silver 5 alloy and aluminum-lanthanum 10 alloy provided by Suzhou Xinghai E-commerce Co., Ltd.; K2ZrF6 and KBF4 provided by Nanning Blue Sky Experimental Equipment Co., Ltd.

[0043] Example 1

[0044] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0045] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0046] S3, melting aluminum block: 618.3g pure aluminum ingot is placed in a graphite crucible and heated to 780°C in a pit-type resistance furnace preheated to 300°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0047] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 20.07g of KBF4 powder and 22.54g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0048] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0049] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0050] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0051] Example 2

[0052] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0053] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0054] S3, melting aluminum block: placing 600.3g pure aluminum ingot in a graphite crucible in a pit-type resistance furnace preheated to 300°C and heating it to 780°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0055] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 60.21g of KBF4 powder and 67.62g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0056] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0057] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0058] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0059] Example 3

[0060] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0061] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0062] S3, melting aluminum block: 582.3g pure aluminum ingot is placed in a graphite crucible and heated to 780°C in a pit-type resistance furnace preheated to 300°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0063] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 100.35g of KBF4 powder and 112.7g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0064] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0065] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0066] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0067] Example 4

[0068] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0069] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0070] S3, melting aluminum block: 564.3g pure aluminum ingot is placed in a graphite crucible and heated to 780°C in a pit-type resistance furnace preheated to 300°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0071] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 140.49g of KBF4 powder and 157.78g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0072] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0073] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0074] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0075] Example 5

[0076] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0077] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0078] S3, melting aluminum block: 618.3g pure aluminum ingot is placed in a graphite crucible and heated to 780°C in a pit-type resistance furnace preheated to 300°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0079] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 20.07g of KBF4 powder and 22.54g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0080] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0081] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0082] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0083] S8, T6 state alloy synthesis: the cast Al-Cu-Mg-Ag-La alloy obtained in step S7 is placed in a muffle furnace and heated to 520°C and kept warm for 6 hours, and quenched in 70°C water to complete solid solution, and the water-quenched sample is placed in a muffle furnace and heated to 170°C and kept warm for 8 hours, and then cooled to room temperature in the furnace to obtain Al-Cu-Mg-Ag-La heat-resistant aluminum alloy.

[0084] Example 6

[0085] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0086] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0087] S3, melting aluminum block: placing 600.3g pure aluminum ingot in a graphite crucible in a pit-type resistance furnace preheated to 300°C and heating it to 780°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0088] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 60.21g of KBF4 powder and 67.62g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0089] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0090] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0091] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0092] S8, T6 state alloy synthesis: the cast Al-Cu-Mg-Ag-La alloy obtained in step S7 is placed in a muffle furnace and heated to 520°C and kept warm for 6 hours, and quenched in 70°C water to complete solid solution, and the water-quenched sample is placed in a muffle furnace and heated to 170°C and kept warm for 8 hours, and then cooled to room temperature in the furnace to obtain Al-Cu-Mg-Ag-La heat-resistant aluminum alloy.

[0093] Example 7

[0094] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0095] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0096] S3, melting aluminum block: 582.3g pure aluminum ingot is placed in a graphite crucible and heated to 780°C in a pit-type resistance furnace preheated to 300°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0097] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 100.35g of KBF4 powder and 112.7g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with a graphite stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0098] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0099] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0100] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0101] S8, T6 state alloy synthesis: the cast Al-Cu-Mg-Ag-La alloy obtained in step S7 is placed in a muffle furnace and heated to 520°C and kept warm for 6 hours, and quenched in 70°C water to complete solid solution, and the water-quenched sample is placed in a muffle furnace and heated to 170°C and kept warm for 8 hours, and then cooled to room temperature in the furnace to obtain Al-Cu-Mg-Ag-La heat-resistant aluminum alloy.

[0102] Example 8

[0103] S1. Cut aluminum-copper alloy, aluminum-magnesium alloy, aluminum-silver alloy and aluminum-lanthanum alloy into small pieces in a machine tool, place them in an electric constant temperature blast drying oven heated to 200°C at a heating rate of 5°C / min, and dry them for 0.5h.

[0104] S2, dehydrating K2ZrF6 powder and KBF4 powder at 300°C for 3h, and mixing them evenly in a mass ratio of 112:120 to obtain a reactant powder;

[0105] S3, melting aluminum block: 564.3g pure aluminum ingot is placed in a graphite crucible and heated to 780°C in a pit-type resistance furnace preheated to 300°C. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt;

[0106] S4, adjusting the temperature of the pit-type resistance furnace to 870°C, adding 140.49g of KBF4 powder and 157.78g of K2ZrF6 powder obtained in step S2 to the aluminum ingot melt in S3, pressing the reactant powder into the melt with a graphite rod, stirring for 30min with an electromagnetic stirrer at a stirring rate of 600r / min, and adding a refining agent to remove the slag;

[0107] S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 800°C, add 97.2g of aluminum-copper 50 alloy and 108g of aluminum-silver 5 alloy dried in S1 in turn, add 8g of covering agent (NaCl:KCl=1:1, mass ratio), let it stand and keep warm for 10 minutes, stir and skim off the slag;

[0108] S6, modification treatment: when the temperature of the pit type resistance furnace drops to 680°C, quickly press 31.5g of aluminum-magnesium alloy and 36g of aluminum-lanthanum 10 alloy dried in S1 into the bottom of the melt for modification treatment, and add 15g of hexachloroethane after keeping warm for 5 minutes. After all the raw materials are completely melted, slag is removed again;

[0109] S7. Synthesis of cast alloy: When the temperature of the pit-type resistance furnace is adjusted to 710°C, mechanical stirring is carried out for 2 minutes, the temperature is increased, and when the furnace temperature is maintained at 730°C, the slag is removed, and the crucible is taken out while maintaining the temperature. The alloy liquid is injected into a mold coated with a mixed coating (sodium silicate: zinc oxide = 1:3, mass ratio) preheated to 200°C in a muffle furnace, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

[0110] S8, T6 state alloy synthesis: the cast Al-Cu-Mg-Ag-La alloy obtained in step S7 is placed in a muffle furnace and heated to 520°C and kept warm for 6 hours, and quenched in 70°C water to complete solid solution, and the water-quenched sample is placed in a muffle furnace and heated to 170°C and kept warm for 8 hours, and then cooled to room temperature in the furnace to obtain Al-Cu-Mg-Ag-La heat-resistant aluminum alloy.

[0111] The effects of the cast alloys provided in the above-mentioned embodiments 1-4 and the T6 heat-resistant aluminum alloys provided in the embodiments 5-8 were verified by the following tests:

[0112] 1. The crystal structures of the alloys provided in the above embodiments and comparative examples were analyzed by X-ray diffraction (XRD):

[0113] Depend on Figure 1 It can be seen from the X-ray diffraction pattern of the cast Al-5.4Cu-0.7Mg-0.6Ag-0.4La-xZrB2 alloy that the alloy is mainly composed of α-Al phase, Al2Cu phase and Al2La phase, and also contains ZrB2 phase and a small amount of Al3Zr phase.

[0114] Depend on Figure 2 It can be seen from the X-ray diffraction pattern of the heat-treated Al-5.4Cu-0.7Mg-0.6Ag-0.4La-xZrB2 alloy that the alloy is mainly composed of α-Al, Al2Cu, Al2La, ZrB2, and a small amount of Al3Zr.

[0115] 2. Verify the mechanical properties of the alloys provided in the above embodiments: Use AGS-X 100KN universal testing machine to test the room temperature and high temperature tensile mechanical properties of the alloy. Room temperature tensile test: The original gauge length of the specimen is 25mm, and the width and thickness of the plate specimen should be measured by taking the average value of the upper, middle and lower three sections, and the stretching speed is 0.5mm / min. High temperature tensile test: The original gauge length of the specimen is 30mm, and the diameter of the bar specimen should be measured by taking the average value of the upper, middle and lower three sections. The specimen is kept at 350°C for 20 minutes and then stretched at a speed of 0.5mm / min. The tensile performance test can obtain the yield strength, tensile strength, etc. of the aluminum alloy at room temperature and high temperature.

[0116] Depend on Figure 3-5 It can be seen that:

[0117] The Vickers hardness of the cast 1ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material provided in Example 1 is 128.1 HV; the tensile strength when stretched at room temperature is 185.9 MPa; and the tensile strength when stretched at 350°C is 93.0 MPa.

[0118] The Vickers hardness of the cast 3ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material provided in Example 2 is 132.3 HV; the tensile strength when stretched at room temperature is 230.9 MPa; and the tensile strength when stretched at 350°C is 102.7 MPa.

[0119] The Vickers hardness of the cast 5ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material provided in Example 3 is 145.9 HV; the tensile strength when stretched at room temperature is 228.6 MPa; and the tensile strength when stretched at 350°C is 105.7 MPa.

[0120] The Vickers hardness of the cast 7ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material prepared in Example 4 is 110.3 HV; the tensile strength at room temperature is 186.7 MPa; and the tensile strength at 350°C is 80.9 MPa.

[0121] Depend on Figure 6-8 It can be seen that:

[0122] The Vickers hardness of the T6 state 1ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material provided in Example 5 is 227.2 HV; the tensile strength when stretched at room temperature is 363.1 MPa; and the tensile strength when stretched at 350°C is 147.8 MPa.

[0123] The T6 state 3ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La provided in Example 6 has a Vickers hardness of 243.6 HV; a tensile strength at room temperature of 446.9 MPa; and a tensile strength at 350°C of 174.4 MPa.

[0124] The Vickers hardness of the T6 state 5ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material provided in Example 7 is 227.6HV; the tensile strength at room temperature is 378.9MPa, and the tensile strength at 350°C is 155.3MPa.

[0125] The Vickers hardness of the T6 state 7ZrB2 / Al-5.4Cu-0.7Mg-0.6Ag-0.4La alloy material provided in Example 8 is 155.4HV; the tensile strength when stretched at room temperature is 309.7MPa; and the tensile strength when stretched at 350°C is 120.1MPa.

[0126] From the above test results, we know that the introduction of ZrB2 improves the Vickers hardness of the alloy material in the cast state, the tensile strength at room temperature, and the tensile strength at high temperature. At the same time, the introduction of the T6 heat treatment process further improves the hardness and tensile strength of the alloy.

[0127] In summary, the introduction of ZrB2 combined with T6 heat treatment not only improves the mechanical properties of Al-Cu-Mg-Ag-La alloy under various temperature conditions, but also expands new possibilities for the application of alloy materials, especially in high temperature environments, which will greatly promote the development of related industrial fields.

[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an Al-Cu-Mg-Ag-La heat-resistant aluminum alloy material, characterized in that: The steps include: S1. Alloy drying: cutting aluminum ingots, aluminum-copper alloys, aluminum-magnesium alloys, aluminum-silver alloys, and aluminum-lanthanum alloys into small pieces in a machine tool and drying them; S2, K2ZrF6 powder and KBF4 powder are dehydrated and mixed to obtain reactant powder; S3, melting aluminum block: placing a pure aluminum ingot in a graphite crucible in a pit-type resistance furnace preheated to 250-300°C and heating it up with the furnace. After the aluminum ingot is completely melted, the surface oxide layer is removed to obtain an aluminum ingot melt; S4, adjusting the temperature of the pit-type resistance furnace, adding the reactant powder obtained in step S2 to the aluminum ingot melt in S3, stirring, and adding a refining agent to remove slag; S5, alloy smelting: adjust the temperature of the pit type resistance furnace to 750-800℃, add the aluminum-copper alloy and aluminum-silver alloy dried in S1 in sequence, add covering agent, let it stand and keep warm for 5-10 minutes, stir and remove slag; S6, modification treatment: when the temperature of the pit-type resistance furnace drops to a certain temperature, the aluminum-magnesium alloy and aluminum-lanthanum alloy dried in S1 are quickly pressed into the bottom of the melt for modification treatment. After keeping warm for 5-10 minutes, hexachloroethane is added. After all the raw materials are completely melted, slag is removed again; S7, as-cast alloy synthesis: adjust the temperature of the pit-type resistance furnace, perform mechanical stirring, heat up, and when the furnace temperature is maintained at a certain temperature, remove the slag, maintain the temperature and take out the crucible, inject the alloy liquid into the preheated mold, cool it, and demold it to obtain the as-cast Al-Cu-Mg-Ag-La alloy; S8, T6 state alloy synthesis: the cast Al-Cu-Mg-Ag-La alloy obtained in step S7 is placed in a muffle furnace and heated to a certain temperature, and the temperature is kept, and cold quenching and solid solution is performed. The water-quenched sample is placed in a muffle furnace and heated to a certain temperature, and the temperature is kept, and then the sample is cooled to room temperature to obtain Al-Cu-Mg-Ag-La heat-resistant aluminum alloy.

2. The preparation method according to claim 1, characterized in that: In step S1, the heating rate of the drying oven is 5-10°C / min, and the metal block is dried in the drying oven at 200°C for 0.5h.

3. The preparation method according to claim 1, characterized in that: In step S2, the K2ZrF6 powder and the KBF4 powder are dehydrated at 250-300° C. for 3 h, and are uniformly mixed in a mass ratio of 112:120 to obtain a reactant powder.

4. The preparation method according to claim 1, characterized in that: In step S3, the pure aluminum ingot is placed in a graphite crucible and heated to 750-800° C. in a preheated pit-type resistance furnace.

5. The preparation method according to claim 1, characterized in that: In step S4, the temperature of the pit-type resistance furnace is adjusted to 870° C., the reactant powder obtained in step S2 is added to the aluminum ingot melt in S3, stirred for 30 minutes at a stirring rate of 600 r / min using a graphite stirrer, and a refining agent is added to remove the slag.

6. The preparation method according to claim 1, characterized in that: In step S6, when the temperature of the pit-type resistance furnace drops to 680-700°C, the aluminum-magnesium alloy and aluminum-lanthanum alloy dried in S1 are quickly pressed into the bottom of the melt for modification.

7. The preparation method according to claim 1, characterized in that: In step S7, when the temperature of the pit-type resistance furnace is adjusted to 700-710°C, mechanical stirring is performed for 2 minutes, the temperature is increased, and the slag is removed when the furnace temperature is maintained at 730-740°C. The temperature is maintained and the crucible is taken out, and the alloy liquid is injected into the preheated mold, cooled, and demolded to obtain a cast Al-Cu-Mg-Ag-La alloy.

8. The preparation method according to claim 1, characterized in that: In step S8, the cast Al-Cu-Mg-Ag-La alloy is placed in a muffle furnace and heated to 520° C. and kept warm for 6 hours, and then quenched in water at 70-100° C. to form a solid solution.

9. The preparation method according to claim 1, characterized in that: In step S8, the water-quenched sample is placed in a muffle furnace and heated to 170° C. and kept at this temperature for 8 h.

10. An Al-Cu-Mg-Ag-La heat-resistant aluminum alloy, characterized in that: Obtained by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fe-Be-contained heat-resisting aluminum copper alloy and manufacturing method of Fe-Be-contained heat-resisting aluminum copper alloy

    CN105441756A

  • Method for preparing high-strength and high-temperature-resistant aluminum-copper alloy material

    CN105925859A